Margin Status and Recurrence in Surgically Treated Patients With HPV+ Oropharyngeal Cancer - Ausburn, Madeleine; Pyne, Justin M; Day, Andrew T; Hajnas, Natalia; Moon, Dominic; Myers, Larry Leonard; Sher, David Jonathan; Truelson, John M; Tillman, Brittny; Sumer, Baran (The Laryngoscope, 2025)
The optimal margins for surgically treated human papilloma virus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) remain undefined. We evaluated the impact of surgical margins on progression-free survival (PFS) in patients with HPV+ OPSCC treated with primary transoral robotic surgery (TORS). Patients undergoing primary TORS from May 2012 to December 2021 for intermediate-risk (T1-T2, resected to clear (≥ 3 mm) or close margins (< 3 mm), and N1-N2) HPV+ OPSCC were included. Survival outcomes were reviewed, and overall and PFS at 3 years posttreatment were determined using Kaplan-Meier analysis. A total of 69 subjects met inclusion criteria. At a median follow-up of 47 months, overall survival (OS) was 100%, and the PFS was 88.9% for the entire subject group. Among subjects not receiving adjunctive radiotherapy (RT), those with close margins had an OS of 100% and a PFS of 100% (median follow-up 47 months). Subjects with clear margins had an OS probability of 100% and a PFS probability of 100% (median follow-up 47 months). In subjects undergoing TORS for HPV+ OPSCC, clear margins did not confer a significant OS or PFS survival advantage compared to those with close margins, even when adjuvant therapy was omitted.